Predictors of prognosis in neonates with congenital diaphragmatic hernia: experience of 12 years - Catarina Granjo Morais; Gustavo Rocha; Filipa Flor-; Paulo Éden; Ana Catarina Fragoso; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2017)
Introduction: Congenital diaphragmatic hernia (CDH) is a severe malformation, displaying relevant mortality and morbidity rates in newborns. Aim: To characterize clinically and demographically all neonatal cases of CDH admitted to a level III Neonatal Intensive Care Unit during a 12-year period and to evaluate the predictive value of baseline characteristics on mortality and morbidity at discharge. Methods: Maternal/infant clinical and electronic records were ret- rospectively reviewed. All neonates with posterolateral CDH admitted between January 2003 and December 2014 were included. Results: Fifty-three newborns were included. Overall mortality during hospitalization was 22/53 (41.5%). Clinical characteristics associated with mortality were the presence of intrathoracic liver (p = 0.005), intrathoracic stomach (p = 0.015), elevated arterial pCO2 or lower pH values at admission (respectively, p = 0.001 and p < 0.001), pre-ductal oxygen saturation < 85% at admission (p = 0.012) and surgical repair with prosthetic patch (p = 0.041). Morbidity at discharge was reported in 7 (22.6%) survivors. Stomach herniation and sepsis were associated with higher morbidity (respectively, p = 0.012 and p = 0.029). In a logistic regression, patch repair was the only variable with predictive value for death during hospitalization, with an odds ratio (OR) of 15 (95% CI 0.98-228.9), and intrathoracic stomach was a predictor of morbidity at discharge (OR = 15.7, 95% CI 1.4-174.2). Conclusion: Structural characteristics, namely defect size and presence of intrathoracic stomach, remain the primary determinants of neonatal prognosis in CDH. Although post-natal approaches have progressively proven their value in increasing survival and improving management of high-risk cases, future researches should continue focusing on the definition of foetal anatomical markers of severity and prenatal treatment of CDH.